198 Should we thrombolyse cognitively impaired patients with acute ischaemic stroke?. Issue 9 (12th August 2022) - Ramnarine, Isabela; Rasheed, Omar; Harkness, Kirsty; Majid, Arshad; Bell, Simon
Abstract : Introduction: Underlying pathological mechanisms of cerebral vessel damage in dementia patients have been suggested to increase the risk of intracranial haemorrhage following thrombolysis for acute ischaemic stroke. This has not been demonstrated in earlier literature. Our study compared the throm- bolysis outcomes of stroke patients with and without cognitive impairment. Methods: A retrospective cohort analysis of stroke patients receiving thrombolysis was conducted. Cognitive impairment was defined as: a diagnosis of dementia, mild cognitive impairment, or clinical evidence of mild cognitive impairment. Outcome measures included haemorrhagic complications, NIHSS and mRS scores, and mortality. Results: Statistical analysis included data from 428 ischaemic stroke patients, 62 of whom had cognitive impairment. Following thrombolysis, cognitively impaired stroke patients had greater increments in dis- ability level, an increased risk of haemorrhagic complications, and a lower likelihood of 90-day survival. Logistic regression modelling revealed the main predictors of these poorer outcomes to be age, time to thrombolysis, and NIHSS on admission. Two thirds of the variance in stroke outcomes remained unex- plained by our models. Conclusion: Confounding variables were the main predictors of poorer thrombolysis outcomes in cogni- tively impaired stroke patients. A large portion of these poorer outcomes remains unexplained, leaving potential for further investigation.